Global, regional, and national burden of headache disorders, 1990–2021, and projections to 2050: a comprehensive analysis of the global burden of disease study 2021 - Shen, Linxue; Li, Hui; Wang, Kuihua; Guo, Ting; Ye, Jianxin (Frontiers in Neurology, 2025)
IntroductionHeadache disorders, including migraines and tension-type headaches, are prevalent and debilitating conditions that affect millions of people worldwide. And this analysis aims to inform evidence-based interventions and policies for alleviating the burden of headache disorders on individuals and societies.MethodsWe analyzed headache data from the Global Burden of Disease Study 2021 report, examining the prevalence, incidence, and disability-adjusted life years across 204 countries and territories over 32 years. The data were stratified according to age, sex, year, geographical region, and socio-demographic Index (SDI). We employed the estimated average percentage change calculation to assess the temporal trends of these indicators. A detailed analysis of health inequities was conducted using decomposition analysis, the pyramid model, slope index, and concentration index. The Bayesian Age-Period-Cohort model was used to forecast the disease burden over the next 26 years.ResultsBy 2021, the global incidence of headache disorders was estimated to be 809.2 million, with tension-type headaches being the most prevalent. Age-standardized incidence rates, prevalence rates, and DALYs have exhibited an overall upward trend since 1990. The health inequality analysis revealed a diminishing disparity in the burden of headache disorders across countries with varying SDI scores. Predictions indicate a continuous increase in headache disorders, potentially reaching over 3.5 billion by 2050 based on current trends.ConclusionThe burden of headache disorders is increasing, with important implications for global health and the economy. The rising predictions highlight the potential need for targeted public health strategies and interventions.